Contemporary sport management - Pedersen, Paul M. (Human Kinetics, 2014)
Provides students with an overview of sport management by presenting extensive discussions of the foundational aspects of the profession and relevant topics on the subject. This text also discusses the role of social media in revolutionising the industry and the significance of sport as an international institution